Diagnostics of COVID-19 Post-Traumatic Anxiety in Students - Aprily, Nuraly Masum; Lestari, Elsa; Rizqi, Anggi Maulana; Mufidah, Zulfin Rachma (International Journal of Educational Qualitative Quantitative Research, 2023)
Post-traumatic anxiety COVID-19 is a state of students after experiencing a pandemic. Post-traumatic anxiety is classified and analyzed based on physical symptoms, emotional symptoms, mental symptoms, behavioral symptoms, spiritual symptoms, and several statements containing conditions that are the condition of post-traumatic COVID-19 students. This study aims to know and find symptoms experienced by students regarding post-traumatic anxiety due to COVID-19. The method used in this study is to use the observation method through data collection by filling out a questionnaire. The sample for this research consisted of 68 students at Anaka State Elementary School, Kawalu sub-district, Tasikmalaya city, Indonesia. Based on the observation results, data was obtained with the most dominant physical symptoms being dizziness, the most dominant emotional symptoms being feeling shaken, the most predominant mental symptoms being forgetfulness, the most dominant behavioral symptoms being crying, and the most dominant spiritual symptoms being grumbling. This research contributes as an overview for teachers and prospective teachers about the condition of students post-COVID and recommends strengthening psychology education to overcome this problem.